Dissertações focalizando a interdisciplinaridade no programa de Pós-Graduação em Educação em Ciências e Matemática da PUCRS : relações entre teoria e prática - Cordeiro, Elise Oliveira (2012)
The Program for Postgraduate in Science and Mathematics Education / PUCRS, in its ten years of existence, have highlighted the importance of the interdisciplinarity and education by research, with which the students are involved from the selection process to the Master course. In this context, the objective of the research was to analyze dissertations about interdisciplinarity, completed in the period between 2004 and 2010. The approach was qualitative, as in the studies analyzed. From an initial survey conducted in search of dissertations available at the PUCRS Central Library, considering the titles of dissertations, keywords and abstracts, the selected papers were submitted to the analysis process, according to the methodology of Discourse Textual Analysis. Each essay describes the monitoring analyzed what happened at all stages of the process, with reflections on the progress and difficulties. At the end of each one, the final considerations allow further theorizing from the initial explanation of relationships between theory and practice. From various teaching methodologies, such as projects, interdisciplinary islands of rationality and learning units, and also in with study groups of Science and Mathematics teachers, was expanded dialogue with other f knowledge areas and the life. In each essay, despite some initial difficulties and resistance to the development of an interdisciplinary work, were verified progress and possibilities of overcoming.